Labours Old and New : the parliamentary right of the British Labour Party 1970-79 and the roots of New Labour. - Meredith, Stephen (Critical labour movement studies series., 2008)
This study is concerned with the?Old? Labour right at a critical juncture of social democratic and Labour politics. It attempts to understand the complex transition from so-called?Old Right? to?New Right? or?New Labour?, and locates at least some of the roots of the latter in the complexity, tensions and fragmentation of the former during the?lean? years of social democracy in the 1970s. The analysis addresses both the short and long-term implications of the emerging ideological, organisational and political complexity and divisions of the parliamentary Labour right and Labour revisionism.